Kajian Eksperimental Penggunaan Ruang Pengering Silinder Vertikal dan Horisontal Mesin Pengering Gabah Tipe Fluidzed Deep - Syarifuddin, Mochammad Arvin; Firman, La Ode M. (Jurnal Media Teknik dan Sistem Industri, 2018)
Abstractâ€” This study explored experimentally the use of vertical and horisontal position of cylindrical drying chamber dryer Fluidzed Deep against temperature distribution, humidity, drying rate, decreasing grain water level, and decreasing grain mass. The method used in this research is design and experiment. This machine uses a burning furnace as a heat source,sengon/ albasia wood as fuel, flat plate type heat exchanger, cyclone to convert wet vapor to dry vapor, filter to dry vapor cleaner, cylindrical drying chamber, blower to blow air, and Jig to support all components. This experiment was carried out three times for the drying chamber in a vertical position, and three times for the drying chamber in a horisontal position. In one drying time, it takes about 270 minutes. In the drying chamber measured temperature and humidity at 12 points of measurement. The results showed that the horisontal cylinder drying chamber produced higher temperature distribution than the vertical cylinder drying chamber, but the temperature distribution was less even, the vertical cylinder dryer produced lower humidity than the horisontal cylinder drying chamber, but resulted in higher deviation than the horisontal cylinder dryer. Drying rate, decrease in grain water content, average grain decrease on average faster than horisontal cylinder. The process of reducing the grain moisture content from about 20% bb to a moisture content of dry milled grains of about 14% bb occurred for 270 minutes or about 4, 5 hours.Â Keyword: Experimental design; Fluized deep dryer; dryer efficiencyÂ